2005
DOI: 10.1248/bpb.28.967
|View full text |Cite
|
Sign up to set email alerts
|

Antihypertensive Potential and Mechanism of Action of Astaxanthin: II. Vascular Reactivity and Hemorheology in Spontaneously Hypertensive Rats

Abstract: Diseases such as hypertension, atherosclerosis, hyperlipidemia, and diabetes are associated with vascular, functional and structural changes including endothelial dysfunction, altered contractility and vascular remodeling. The role of vascular endothelium in modulating vascular tone and maintaining cardiovascular homeostasis in blood vessels, through the production of an array of both relaxant (e.g., nitric oxide [NO], prostacyclin) and constrictor factors (such as thromboxane, endothelin), has been widely rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
36
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 25 publications
3
36
1
Order By: Relevance
“…Subsequently, Hussein et al [74] showed that astaxanthin might modulate the blood fluidity in hypertension, and the antihypertensive effects of astaxanthin might be exerted through mechanisms including normalization of the sensitivity of the adrenoceptor sympathetic pathway, particularly a-adrenoceptors, and by restoration of the vascular tone through attenuation of the angiotensin II-and reactive oxygen species-induced vasoconstriction. In the succedent experiment, Hussein et al [8] further found that astaxanthin significantly reduced the plasma level of NO À 2 and NO À 3 , an indicator of the endogenous formation of NO, and definitive structural alterations in the coronary artery and aorta of spontaneously hypertensive rats were ameliorated by astaxanthin, suggesting that astaxanthin could modulate the oxidative condition and might improve vascular elastin and arterial wall thickness in hypertension.…”
Section: Cardiovascular Protective Effectmentioning
confidence: 99%
“…Subsequently, Hussein et al [74] showed that astaxanthin might modulate the blood fluidity in hypertension, and the antihypertensive effects of astaxanthin might be exerted through mechanisms including normalization of the sensitivity of the adrenoceptor sympathetic pathway, particularly a-adrenoceptors, and by restoration of the vascular tone through attenuation of the angiotensin II-and reactive oxygen species-induced vasoconstriction. In the succedent experiment, Hussein et al [8] further found that astaxanthin significantly reduced the plasma level of NO À 2 and NO À 3 , an indicator of the endogenous formation of NO, and definitive structural alterations in the coronary artery and aorta of spontaneously hypertensive rats were ameliorated by astaxanthin, suggesting that astaxanthin could modulate the oxidative condition and might improve vascular elastin and arterial wall thickness in hypertension.…”
Section: Cardiovascular Protective Effectmentioning
confidence: 99%
“…Astaxanthin from H. pluvialis has also been shown to reduce blood pressure 7,48,49 . Hussein et al 48 suggest that 5mg/kg/day of dietary astaxanthin given to hypertensive rats for 7 weeks modulates blood fluidity in hypertension and that its antihypertensive effect may be due to mechanisms that include the normalization of adrenoceptor sensitivity and the restoration of vascular tonus by attenuating the vasoconstriction induced by reactive oxygen species and angiotensin II.…”
Section: Astaxanthin and Chronic Diseasesmentioning
confidence: 99%
“…Hussein et al 48 suggest that 5mg/kg/day of dietary astaxanthin given to hypertensive rats for 7 weeks modulates blood fluidity in hypertension and that its antihypertensive effect may be due to mechanisms that include the normalization of adrenoceptor sensitivity and the restoration of vascular tonus by attenuating the vasoconstriction induced by reactive oxygen species and angiotensin II. The administration of a higher dose (50 mg/kg/day) for a period of 22 weeks in obese rats reduced not only blood pressure but also other symptoms of the metabolic syndrome.…”
Section: Astaxanthin and Chronic Diseasesmentioning
confidence: 99%
“…15,16) We previously investigated the blood pressure (BP) lowering effect of a dietary astaxanthin (ASX-O) in spontaneously hypertensive rats (SHR) 17) and its suggested action mechanisms. 18) In the present study, the effects of ASX-O on the oxidative status and the vascular physiology in SHR were examined. We measured the levels of nitrite/nitrate (NO 2 Ϫ /NO 3 Ϫ ) anions and lipid peroxidation in ASX-O-treated SHR.…”
mentioning
confidence: 97%